Circulating Tumor Cell Is a Clinical Indicator of Pretransplant Radiofrequency Ablation for Patients with Hepatocellular Carcinoma. (19th October 2021) - Chen, Zhitao; Wang, Tielong; Chen, Chuanbao; Hong, Xitao; Yu, Jia; Ma, Yihao; Guo, Yiwen; Huang, Changjun; He, Xiaoshun; Ju, Weiqiang; Chen, Maogen
Abstract : Introduction . It is of great significance to confirm reliable indicators for the guidance of pretransplant radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC). In this study, we aim to investigate whether circulating tumor cell (CTC) status is a clinical indicator for RFA before liver transplantation (LT) in HCC patients. Method . CTC analyses were measured in 79 HCC patients. Clinical outcomes including progression-free (PFS) and overall survival (OS) were compared and analyzed between patients with and without pretransplant RFA. Result . Forty-two patients were detected as CTC-positive and 18 patients received pretransplant RFA. Recurrence was correlated with CTC count (P = 0.024 ), tumor number (P = 0.035 ), liver cirrhosis (P = 0.001 ), Milan criteria (P = 0.003 ), and University of California San Francisco (UCSF) criteria (P = 0.001 ). Kaplan–Meier analysis revealed that patients with CTC-positive had a lower PFS rate (P = 0.0257 ). For CTC-positive patients, the PFS rate of the pretransplant RFA group was significantly higher than the non-pretransplant RFA group (100% vs. 46.7%, P = 0.0236 ). For CTC-negative patients, both PFS rate and OS rate were similar and without significant differences. In multivariate analysis, pretransplant RFA was the independent factor for PFS (P = 0.025 ). Conclusion . Pretransplant CTC status can guide the administration of pretransplant RFA in HCC patients which can improve PFS in CTC-positive HCC patients.